Turkish plural nouns are number-neutral: Experimental data - Renans, Agata; Tsoulas, George; Folli, Rafaella; Ketrez, Nihan; Tieu, Lyn; de Vries, Hanna; Romoli, Jacopo (Proceedings of the Amsterdam Colloquium, 2025)
Across languages, plural marking on a noun typically conveys that there is more than one entity in the denotation of the noun. In English, this ‘more than one’ meaning is generally regarded as an implicature on top of a ‘semantically unmarked’/number-neutral literal meaning of the plural noun ([10, 18, 20]; see also [5, 12]). In Turkish, however, it is controversial whether plural nouns should be analysed as number-neutral or whether they should directly denote strict plurality [2, 19, 6]. This debate is important as it can shed light on the meanings number marking can have across languages, thereby constraining cross-linguistically adequate theories of the semantics of number. We tested Turkish speaking adults and 4–6-year-old children on the interpretation of plurals in upward- and downward-entailing contexts, as compared to the ‘not all’ scalar inference of bazı ‘some’. The results of our experiment support a theory of plural nouns which includes a number neutral interpretation.